Proper Names as the Category of Non-Equivalent Lexis and the Peculiarities of their Translation into Russian (on the material of Chinese Folk and Author Tales) - Olga N. Boldyreva; Elena P. Khudogulova; Wu Mengzhu (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2018)
The article is devoted to the study of Chinese fairy-tales “Why the salt water in the sea”, “The Liu brothers”, “The Yellow Stork”, “Why dogs do not like cats”, “Golden Fish”, where proper names are distinguished and their features are analyzed as categories of equivalent vocabulary. The purpose of the article is to show that translations of Chinese proper names cannot be carried out in accordance with the principle of maximum ratio of lexical units and parallelism of syntactic constructions, which is explained by typological differences between languages, expressed both in the specifics of the vocabulary and in the singularity of the syntax. Though having a certain translation experience and a good knowledge of the original language, it is possible to solve the tasks that face the interpreter successfully.